2021
DOI: 10.1108/jbim-01-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge interconnection process: evidence from contract manufacturing relationships

Abstract: Purpose The main goal of the paper is to describe the knowledge interconnection process embedded in an interactive business relationship. The purpose of this study is to understand the knowledge interconnection inside the supplier-buyer relationship in the field of contract manufacturing. The knowledge interconnection process is defined by the authors as a process linked to business relationships, which contains different types of knowledge and various sub-processes related to them. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
(32 reference statements)
0
9
0
2
Order By: Relevance
“…Mandják et al. (2021) studied the knowledge interconnection process and found that it has implications for the network. Knowledge exists on several layers in an organization; it can be at the individual, group, project or firm level (Brady and Davies, 2004; DeFillippi and Arthur, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mandják et al. (2021) studied the knowledge interconnection process and found that it has implications for the network. Knowledge exists on several layers in an organization; it can be at the individual, group, project or firm level (Brady and Davies, 2004; DeFillippi and Arthur, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, we followed an abductive approach since our research process has not been linear but has involved continually going back and forth between empirical observations and theory. As such, our research involved refining an initial research goal and conceptual framework during the process (Mandják et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In this research, we adopted a single case study approach since, according to Mandj ak et al (2021Mandj ak et al ( , p. 1582, it:…”
Section: Methodsmentioning
confidence: 99%
“…The resulting networks aimed at joint development are called innovation networks, where resources owned by different network members are used for a common goal (corsaro et al, 2012). The interaction between the parties plays a key role in the acquisition of knowledge and resources (Mandják et al 2021) In accordance with the evolutionary economics approach (Pyka, 2002), the actors strive to cooperate with other actors with heterogeneous competences, because in the accelerated competitive situation, they can thus acquire the knowledge necessary for development in the most efficient way.…”
Section: Innovation Network and Electricity Network Innovationmentioning
confidence: 99%